2022
DOI: 10.1186/s12913-022-08034-x
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and the role of authentic leadership in academic medicine

Abstract: Background Recently, there has been increasing evidence that reducing burnout in healthcare providers requires significant organizational efforts that include the integration of leadership strategies. Methods Focus groups were conducted across four health systems within the University of Colorado Department of Medicine in four affinity groups (administrative staff, medical trainees, research faculty, and clinical faculty). Authentic leadership the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
(31 reference statements)
0
4
0
2
Order By: Relevance
“…For example, Zainab et al ( 2021) demonstrated the impact of transformational leadership and transparent communication on employees' openness to change, highlighting the crucial role of trust and communication in promoting positive organizational outcomes. Similarly, Mcpherson et al McPherson et al (2022) emphasized the importance of leadership styles that encourage relationship transparency, openness, and support in addressing burnout symptoms in academic medicine. Moreover, Bäckström et al (2016) discussed how communicative leadership, characterized by openness and dialogue with employees, can improve organizational effectiveness and governance in healthcare settings.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Zainab et al ( 2021) demonstrated the impact of transformational leadership and transparent communication on employees' openness to change, highlighting the crucial role of trust and communication in promoting positive organizational outcomes. Similarly, Mcpherson et al McPherson et al (2022) emphasized the importance of leadership styles that encourage relationship transparency, openness, and support in addressing burnout symptoms in academic medicine. Moreover, Bäckström et al (2016) discussed how communicative leadership, characterized by openness and dialogue with employees, can improve organizational effectiveness and governance in healthcare settings.…”
Section: Resultsmentioning
confidence: 99%
“…According to McPherson and colleagues, leadership styles that promote relationship transparency, openness, and support may help address the demands in academic medicine, including the symptoms of burnout. 37 …”
Section: Interventions To Mitigate Burnoutmentioning
confidence: 99%
“…Conocido también como síndrome de desgaste profesional o síndrome del quemado, es una condición de deterioro de la salud mental relacionada directamente con el trabajo que afecta a sujetos sin antecedentes de trastornos psicológicos (McPherson et al, 2022). Las tres dimensiones del síndrome son: cansancio emocional (agotamiento), ineficiencia (incapacidad de enfrentamiento) y cinismo (irritabilidad) (Maslach & Leiter, 2016).…”
Section: Síndrome De Burnoutunclassified
“…El estrés en el entorno sanitario ha aumentado de manera abismal, el agotamiento está alcanzando proporciones epidémicas en los profesionales sanitarios (McPherson et al, 2022). En un estudio encuestaron a 1122 veterinarios de pequeños animales sobre satisfacción profesional y burnout en Estados Unidos y Canadá; el resultado de la encuesta fue que el 49% reportó agotamiento.…”
Section: Prevalenciaunclassified